Syadd Al-Żarāi’ dan Qiyās sebagai Metode Ijtihad dalam Fatwa Boikot Produk Yahudi - Abdillah, Nanang (Program Studi Hukum Ekonomi Syariah, 2024)
The invasion of Israel into Palestine, especially in areas considered historically and religiously significant, such as Jerusalem, can be seen as disregarding the humanitarian values established by Islam. This deeply hurts the feelings of the Muslim community specifically and ignores the calls for peace from the international community in general. Reaction of Muslim Community to this conflict is very serious. As a form of religious solidarity, they express condemnation of Israel by boycotting Jewish products. This is aimed at resisting Israel's military aggression against Palestine. From a jurisprudential perspective, this can be justified by referring to the Fatwa of the Indonesian Ulama Council (MUI) Number 83 of 2023, supported by Nahdlatul Ulama (NU) and Muhammadiyah. The opinions of scholars in several fiqh books also tend to prohibit transactions with belligerent non-Muslims. From the standpoint of uṣūl fiqh (principles of Islamic Jurisprudence), the fatwa on boycotting Jewish products can be justified because it fulfills the elements of relevant ijtihad methods, namely syadd al-żarāi’ and qiyās.